MATHE - Rekonstruktionen

...komplette Frage anzeigen

1 Antwort

d = 0, da (0 | 0) ∈ f

  • y = ax³ +bx² + cx
  • y' = 3ax² + 2bx + c;
  • y'' = 6ax + 2b

y'' = 0 für x = 2, also

12a + 2b = 0;

b = -6a (1)


y' = -3 für x = 2, also

-3 = 3a * 4 + 2b * 2 + c =

mit (1):

12a + 4(-6a) + c =

-12a +c;

c = -3 +12a = 3(4a -1); (2)


y = 4 für x = 2, also mit (1) und (2):

4 = a8 +(-6a)4 + 3(4a -1)2;

a = 5/4

mit (1):

b = -6a = -15/2

mit (2):

c = 3(4a-1) = 12

y = 5x³/4 -15x²/2 +12x

Was möchtest Du wissen?